Implementasi Strategi Diskusi untuk Meningkatkan Hasil Belajar Fiqih di MIN 13 Magetan - Luthfiyatul Hanifah (Moral : Jurnal kajian Pendidikan Islam, 2024)
Learning is an active process carried out by individuals to experience behavioral changes through interaction with their surrounding environment. This study aims to improve the learning outcomes of Fiqh subjects for grade IV students of MIN 13 Magetan in the 2023/2024 academic year, especially on the material of the five obligatory prayers, through the application of discussion strategies in learning. The problem raised in this study is the low learning outcomes of students who have not reached the Minimum Completion Criteria (KKM). This research was conducted from March to April 2023 with the subject of teachers as implementers of discussion strategies and 40 grade IV students as students. The method used is Classroom Action Research (CAR), supported by observation data through assessment sheets. The results of the study showed that discussion strategies were effective in improving learning outcomes. In cycle I, the percentage of student learning completion classically reached 70% and was classified as incomplete. However, in cycle II there was an increase to 80%, which was included in the complete category. Thus, it can be concluded that the implementation of discussion strategies can have a positive impact on improving the Fiqh learning outcomes of grade IV students at MIN 13 Magetan in the 2023/2024 academic year.